2009
DOI: 10.1111/j.1365-2214.2008.00888.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of childhood sexual abuse among Mexican adolescents

Abstract: In the population studied, the prevalency of child sexual abuse was greater than that reported in Mexico City (4.3-8.4%), although it was similar to that found in the Spanish child population (15-23%). The risk of sexual abuse is greater for girls and the principal aggressors are male neighbours, family friends and relatives; the abuse is committed in the home of the aggressor or the victim and very few cases are reported to the authorities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
15
2
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 24 publications
8
15
2
6
Order By: Relevance
“…In this study, the most common forms of CSA were being ''shown pictures or movies of people doing sexual things'', ''touched your body in a sexual way'', ''kissed when you didn't want to be kissed'', ''touched your private parts'' and ''opened or took their clothes off in front of you when they should not have done so''. These experiences have also been reported consistently in other studies (Chen et al, 2006(Chen et al, , 2004Madu & Peltzer, 2000;Olley, 2008;Pineda-Lucatero et al, 2009), suggesting that these forms of CSA are not uncommon among adolescents, both in developed and developing countries such as Zimbabwe.…”
Section: Prevalence Of Csasupporting
confidence: 56%
See 1 more Smart Citation
“…In this study, the most common forms of CSA were being ''shown pictures or movies of people doing sexual things'', ''touched your body in a sexual way'', ''kissed when you didn't want to be kissed'', ''touched your private parts'' and ''opened or took their clothes off in front of you when they should not have done so''. These experiences have also been reported consistently in other studies (Chen et al, 2006(Chen et al, , 2004Madu & Peltzer, 2000;Olley, 2008;Pineda-Lucatero et al, 2009), suggesting that these forms of CSA are not uncommon among adolescents, both in developed and developing countries such as Zimbabwe.…”
Section: Prevalence Of Csasupporting
confidence: 56%
“…Existing discrepancies in prevalence estimates of CSA can be attributed to methodological variations in relation to such issues as sampling, definition of CSA, method of administration, age restriction and questionnaire design (Leventhal, 1998;Priebe & Svedin, 2009;Pineda-Lucatero et al, 2009). While there is no universal definition of CSA, few studies have adopted previously validated definitions.…”
Section: Introductionmentioning
confidence: 99%
“…A study which surveyed 1,067 Mexican junior high students about their experiences of CSA found that of the 18.7 per cent (n¼200) who had experienced CSA, 50 per cent of the offenders were neighbours, 36.8 per cent relatives, and 13.9 per cent strangers (Pineda-Lucatero et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Other studies have asked about the victim's age when the abuse occurred and a range of specific questions related to the type of sexual abuse (Pineda-Lucatero et al, 2009). These additional questions may be partially responsible for the higher rates reported in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…These adolescents reported a rate of 18.7%. Additional questions included age when the abuse occurred, relation to the aggressor, duration of the abuse and whether the abuse was reported (Pineda-Lucatero, TrujilloHernandez, Millan-Guerrero, & Vasquez, 2009). A study carried out among women below 18 years of age in six countries in Sub-Saharan Africa, in which CSA was defined as "ever being forced to have sexual intercourse or perform any other sexual act", reported CSA prevalence rates that ranged between 1.0 and 5.8 (Yahaya, Ponce de Leon, Uthman, Soares, & Macassa, 2014).…”
Section: Introductionmentioning
confidence: 99%